Pengaruh Model Pembelajaran Kontekstual Terhadap Hasil Belajar Peserta Didik Kelas VIII SMPN 22 Mataram Tahun Pelajaran 2025/2026 - Hasnawati Hasnawati; Muhammad Turmuzi; Tabita Wahyu Triutami Triutami (FKIP Universitas Mataram, 2026)
Contextual learning is directly related to real phenomena. This motivates students to learn more actively, encourages them to think critically, and makes the knowledge learned more meaningful and easy to apply in everyday life. In fact, in learning, students only see, hear and write materials so that learning outcomes are low. This study aims to empirically test the effect of the contextual learning model on the learning outcomes of class VIII students of SMPN 22 Mataram in the 2025/2026 Academic Year. The subjects in this study were class VIII students at SMPN 22 Mataram who were distributed into 2 groups of 43 people, each VIII A with 21 people and VIII B with 22 people. Data collection was carried out using learning outcome tests and student and teacher observation guidelines. The data analysis technique used was the independent sample t test (polled variance). The results of the analysis showed that there was a significant influence of the contextual learning model on the learning outcomes of class VIII students of SMPN 22 Mataram in the 2025/2026 Academic Year. This is indicated by a statistically significant average difference between the two groups with a t-test value of 6.875 > t table 1.681 significance of 0.000 < 0.05. The category of contextual learning influences learning outcomes very significantly with an effect size of 5.74 > 0.8. The results of this study are expected to not only be a theoretical study, but can be implemented in real terms as an applicable solution in overcoming problems in mathematics learning.